THE TYPOLOGY OF TRADITIONAL SLAVIC HOUSES, A CASE STUDY OF SERBIA - Ana Momčilović-Petronijević; Biljana Arandjelović (AR: Arhitektura, Raziskave, 2013)
Traditional Slavic houses were built of non-permanent materials using primitive construction techniques. It is possible to learn about them from literature sources of primarily an ethnographic or historical nature, directly on the basis of very rare surviving examples, though these are in considerably poor conditions and through the remaining folklore. Houses built by South Slavs when they settled in the Balkan Peninsula were single-roomed. Their first houses had a resemblance to the primitive homes in their wooded Carpathian homeland, at least in those regions of the Balkans that were rich in forests. The first forms of houses in Serbia were single-roomed houses, which were further developed during the Turkish rule in Serbia (1454-1878). The paper gives a chronological overview, from the earliest types of traditional houses to better developed traditional architecture in Serbia.